Analisis Hak dan Kewajiban Guru di Era Society 5.0 - Cherry Auralia; Anggi Desvita Sari; Layla Amalya; Adelia Ramadhani; Rully Hidayatullah; Hadeli Sikumbang (Journal Educational Research and Development | E-ISSN : 3063-9158, 2025)
The term "Profession" originates from the Latin word Professus, meaning a public declaration to carry out a specific duty. It refers to an occupation that requires expertise, advanced education, and a high level of moral and social responsibility. According to the Indonesian Dictionary (KBBI), a profession is a field of work based on education and professional integrity. Teaching, as a profession, holds a strategic role within the education system, where teachers serve as character educators and learning facilitators responsible for the intellectual and moral development of students. Teachers are required to possess pedagogical, professional, social, and personal competencies as mandated by Law No. 14 of 2005. The concept of Society 5.0, introduced by Japan, emphasizes the integration of technology with human values. In the context of education, it demands a transformation of the learning system and the role of teachers. Teachers are expected to master technology and use it to shape students' character and creativity. This study uses a literature review approach to analyze the rights and responsibilities of teachers in the era of Society 5.0 . The findings show that teachers have professional, economic, academic, technological, social, and participatory rights. They also face growing responsibilities, such as enhancing digital competencies, innovating teaching methods, strengthening character education, and collaborating with various stakeholders to support holistic education.